2019
DOI: 10.1002/cbin.11267
|View full text |Cite
|
Sign up to set email alerts
|

Vibration activates the actin/NF‐κB axis and upregulates IL‐6 and IL‐8 expression in human periodontal ligament cells

Abstract: We previously reported that mechanical vibration‐induced proinflammatory cytokines, interleukin‐6 (IL‐6) and IL‐8, expression in human periodontal ligament (hPDL) cells, however, the underlying mechanism remained unclear. Mechanical stimuli are able to activate cellular responses by inducing the activation of several signaling pathways including cytoskeletal changes and inflammation. The actin cytoskeleton is a highly dynamic network and plays many important roles in intracellular events. Here, we aimed to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…For example, the application of CTS with 10% elongation and a frequency of 1 Hz yielded an increased the level of IL-6 in primary human PDL cells within the first 2- or 6 h of strain [ 48 ]. Similar observations with an increased IL-6 have been made with the application of static tension [ 57 ], hydrostatic pressure (HP) [ 26 ], or vibration with 30 Hz [ 63 ]. Moreover, IL-8 expression was up-regulated under the application of 3 ~ 15% cyclic stretching with a frequency of 0.2 Hz after 24 h [ 49 ].…”
Section: Discussionsupporting
confidence: 63%
“…For example, the application of CTS with 10% elongation and a frequency of 1 Hz yielded an increased the level of IL-6 in primary human PDL cells within the first 2- or 6 h of strain [ 48 ]. Similar observations with an increased IL-6 have been made with the application of static tension [ 57 ], hydrostatic pressure (HP) [ 26 ], or vibration with 30 Hz [ 63 ]. Moreover, IL-8 expression was up-regulated under the application of 3 ~ 15% cyclic stretching with a frequency of 0.2 Hz after 24 h [ 49 ].…”
Section: Discussionsupporting
confidence: 63%
“…Studies 19,20 have found that FCγR1 maintains the activated state of neutrophils by PI3K after binding to the immune complex. In addition, IL‐8 is also a downstream target for the known PI3K‐NF‐κB signalling pathway, 21–23 and we found that HRG inhibits the conduction of the PI3K and NF‐κB signalling pathways and reduces the production of downstream IL‐8. We found that the use of anti‐FCγR1 antibody eliminated the effects of HRG on the PI3K and NF‐κB signalling pathways and IL‐8 (Figures 4G and H), further demonstrating that HRG inhibits PI3K and the NF‐κB signalling pathway by binding to the FCγR1 receptor and thus affects neutrophil chemotaxis.…”
Section: Resultsmentioning
confidence: 74%
“…ABPs help regulate the actin skeleton polymerization. This modulation can [64]. For example, Arp2/3 complex-dependent actin skeleton remodeling is important for B cell activation to alleviate inflammatory responses [65].…”
Section: Abps In Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…ABPs help regulate the actin skeleton polymerization. This modulation can activate inflammation-related NF- κ B signaling pathways and subsequently upregulate the expression of IL-6 and IL-8 in inflammatory diseases, such as periodontal ligament tissue inflammation [ 64 ]. For example, Arp2/3 complex-dependent actin skeleton remodeling is important for B cell activation to alleviate inflammatory responses [ 65 ].…”
Section: Abps In Chronic Inflammatory Diseasesmentioning
confidence: 99%